La peinture des paysages dans les lais bretons moyen-anglais - Marie-Françoise Alamichel (Etudes Epistémè)
Description is uncommon in Old or Middle English texts. The works under study in this special issue confirm this statement. They are an invitation to some literary journeys between chivalric romances and lays – two different forms which seem to be opposed in many ways (action, military deeds, focus on the hero for the former and the use of supernatural, fairy-world motifs as well as the importance of social and family interaction for the latter) including their approach to space and the depiction of landscapes (respectively emphasizing verticality and horizontality). The 14th century-texts, however, show that description had by then been (timidly) introduced so that one can relate the oldest works of the collection to romanesque style (limited colour palette, juxtaposition and parataxis, strict code of conventions and symbols), and the more recent ones to gothic art (greater variety of colours, naturalism, close-ups on details, movement, perspective [foreground/background]).